Wave Attenuation by Vegetation: Model Implementation and Validation Study - Abdolali, Ali; Hesser, Tyler J.; Anderson Bryant, Mary; Roland, Aron; Khalid, Arslaan; Smith, Jane; Ferreira, Celso; Mehra, Avichal; Sikiric, Mathieu Dutour (Frontiers in Built Environment, 2022)
The wave-vegetation interaction is implemented in the WAVEWATCH III (WW3) model. The vegetation sink term follows the early formulations of Dalrymple et al. (1984) focused on monochromatic waves and vegetation approximated as an array of rigid, vertical cylinders and later expanded by Mendez and Losada (2004) for random wave transformations over mildly sloping vegetation fields under breaking and nonbreaking conditions assuming a Rayleigh distribution of wave heights. First, validation is carried out for 63 laboratory cases (Anderson and Smith, 2014) with homogeneous vegetation fields for single and double-peak wave spectra. Then, a field case application is conducted to assess the wave attenuation in a wetland environment with spatially variable vegetation fields during stormy conditions. The case study uses data collected at Magothy Bay located in Chesapeake Bay during Hurricanes Jose and Maria 2017, USA, during Hurricanes Jose and Maria 2017. The domain decomposition parallelization and the implicit scheme have been used for the simulations to efficiently resolve complex shorelines and high-gradient wave zones, incorporating dominant physics in the complicated coastal zone including wave breaking, wave-current interaction, bottom friction and scattering, wave-vegetation interaction and nonlinearity. (Abdolali et al., 2020). The lab validation and field application demonstrate that WW3 is an effective tool for evaluating the capacity of wetland natural or nature-based features to attenuate wave energy to achieve coastal flood risk reduction.